Circumscription, diagnosis and description of a subfamily of Australo-Papuan robins - Loynes, Kate; Joseph, Leo; Keogh, J. Scott (Zootaxa, 2011)
The family-group name Microecinae Loynes, Joseph and Keogh, 2009 was erected by Loynes et al. (2009) following their phylogenetic analysis of the Australo-Papuan robins (Aves: Passeriformes: Petroicidae). Loynes et al. (2009) assigned to Microecinae one genus Microeca Gould, 1840, which as conventionally construed (see Boles 2007) comprises six species (M. flavigaster, M. fascinans, M. griseoceps, M. hemixantha, M. flavovirescens, M. papuana) found in Australia, New Guinea and some surrounding islands (see Schodde and Mason 1999, Boles 2007 for details). Loynes et al. (2009) were able to include only the first three of those six species in their analysis. They did, however, transfer a further species from Eopsaltria to Microeca, which was thus recognized as M. flaviventris.